Caspofungin and Polymyxin B Reduce the Cell Viability and Total Biomass of Mixed Biofilms of Carbapenem-Resistant Pseudomonas aeruginosa and Candida spp. - Fernandes, Luciana; Fortes, Bruna Nakanishi; Lincopan, Nilton; Ishida, Kelly (Frontiers in Microbiology, 2020)
Pseudomonas aeruginosa and Candida spp. are biofilm-forming pathogens commonly found colonizing medical devices, being mainly associated with pneumonia and bloodstream infections. The coinfection by these pathogens presents higher mortality rates when compared to those caused by a single microbial species. This study aimed to evaluate the antibiofilm activity of echinocandins and polymyxin B (PMB) against polymicrobial biofilms of carbapenem-resistant (CR) P. aeruginosa and Candida spp. (C. albicans, C. parapsilosis, C. tropicalis and C. glabrata). In addition, we tested the antimicrobial effect on their planktonic and monomicrobial biofilm counterparties. Interestingly, beyond inhibition of planktonic (MIC= 0.5 µg/mL) and biofilm (MBIC50= ≤ 2-8µg/mL) growth of P. aeruginosa, PMB was also effective against planktonic cells of C. tropicalis (MIC = 2 µg/mL), and polymicrobial biofilms of CR P. aeruginosa with C. tropicalis (MBIC50 ≤ 2µg/mL), C. parapsilosis (MBIC50= 4-16 µg/mL), C. glabrata (MBIC50 = 8-16 µg/mL) or C. albicans (MBIC50 = 8-64 µg/mL). On the other hand, while micafungin (MFG) showed highest inhibitory activity against planktonic (MIC≤ 0.008-0.5 µg/mL) and biofilm (MBIC50 ≤ 2-16µg/mL) growth of Candida spp.; caspofungin (CAS) displays inhibitory activity against planktonic cells (MIC= 0.03-0.25 µg/mL) and monomicrobial biofilms (MBIC50 ≤2-64µg/mL) of Candida spp., and notably on planktonic and monomicrobial biofilms of CR P. aeruginosa (MIC or MBIC50 ≥ 64 µg/mL). Particularly, for mixed biofilms, while CAS reduced significantly viable cell counts of CR P. aeruginosa and Candida spp. at ≥32 and ≥2 µg/mL, respectively; PMB was effective in reducing viable cells of CR P. aeruginosa at ≥2 µg/mL, and Candida spp. at ≥8 µg/mL. Similar reduction of viable cells was observed for CAS (32-64 µg/mL) and PMB (2 µg/mL). These findings highlight the potential of PMB and CAS for the treatment of polymicrobial infections caused by Candida spp. and critical priority carbapenem-resistant P. aeruginosa.